Ten years trend analysis of malaria cases at rural health and training centre Mandur, Goa - Narathattil, Akhila; Desai, Archana; Ferreira, A. M.; Bicholkar, Abhishekh (International Journal Of Community Medicine And Public Health, 2020)
Background: Malaria is a complex disease that varies widely in epidemiology in different parts of the world. Through its strategic action plan for malaria control (2007-2012) and its updated national drug policy on malaria India has put a strong pillar to address malaria prevention and control. The purpose of the study is to evaluate the hospital-based proportion of fever cases being diagnosed as malaria and determine its trend. Methods: A retrospective record-based study was carried out at rural and health training centre at Mandur. All suspected fever cases were reported to the centre sent for peripheral blood examination. Results: A total of 6073 patients who had clinical history suggestive of malaria were examined for malaria parasites. Out of 6073 slides examined, 187 slides were positive for malarial parasites. Out of 187, 136 (72.7%) were Plasmodium vivax, 40 (21.3%) were Plasmodium falciparum and 13 (16.9%) were mixed infections. Of the 187 patients positive for malaria 155 (82.9%) were males and 32 (17.1%) were females. Maximum number of malaria cases i.e., 63 (33.7%) were in the age group 21 to 30 years. Out of 187 cases, maximum number of cases were reported during a period of 5 months (July to November), very minimum (10) microscopically confirmed malaria cases reported in 2014. Maximum (36) no microscopically confirmed malaria cases were found in 2013. Conclusions: In the studied area Plasmodium vivax is the most common type and it was more in males than females, most affected age group was between 21-30 years.